Accounting for Efficiency: Productivity Assessment of Merged Hospitals in Portugal Using DEA–Malmquist Analysis - Natália Maria Pereira Macedo; Anabela Martins Silva; Amélia Silva (World, 2025)
This study analyses the effects of public hospital mergers in Portugal, particularly the creation of hospital centers, on productivity levels. Grounded in the theoretical frameworks of New Public Management and Efficiency Theory, a Data Envelopment Analysis (DEA) approach, combined with the Malmquist Productivity Index, was used to evaluate performance. Results for the 2013–2015 period show no statistically significant difference in productivity levels between merged hospitals (hospital centers) and non-merged hospitals (hospital units). However, for hospitals merged in 2007, there is evidence of significant productivity gains in the post-merger period (2008–2014). These findings partially support the assumptions of New Public Management and Efficiency Theory concerning efficiency improvements through hospital mergers in the public sector.